Manajemen pembinaan qira'ah al-qur’an untuk meningkatkan kualitas bacaan al-qur’an mahasantriah di Ma’had Al-Jami’ah UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan - Ulfah, Maria; Zulhimma, Zulhimma; Daulay, Muhammad Roihan (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2025)
This study is motivated by the variation in the quality of Qur’an recitation among female students (mahasantriah). The research aims to analyze the management of Qira’ah Al-Qur’an mentoring at Ma’had Al-Jami’ah, UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, by examining the functions of management: planning, organizing, implementing, supervising, and evaluating. The research employs a descriptive qualitative approach, with data collected through observation, in-depth interviews, documentation studies, and continuous evaluation. The findings indicate that the management of Qira’ah Al-Qur’an mentoring has been implemented effectively and in a structured manner, starting from planning based on placement tests, clear organization of human resources, scheduled instructional activities, to a tiered system of supervision and evaluation. This implementation contributes significantly to improving the quality of Qur’an recitation among the mahasantriah, especially in the aspects of makharijul huruf, fluency, and mastery of tajwid. However, the study also identifies the need for innovation in instructional methods and the development of more standardized evaluation instruments to achieve more optimal outcomes. It is hoped that these findings can serve as a reference for the development of Qur’an mentoring programs in similar educational institutions.